2007
DOI: 10.1007/s12098-007-0109-8
|View full text |Cite
|
Sign up to set email alerts
|

Obesity amongst affluent adolescent girls

Abstract: There is significant prevalence of obesity in affluent schoolgirls in Delhi and more than half of them have central obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 15 publications
2
26
1
Order By: Relevance
“…9 Another study among affluent girls in Delhi reported the prevalence of obesity and overweight to be 5.3 and 15.2%, respectively. 10 Similar studies had been conducted to assess the prevalence of overweight and obesity in India and the results are comparable to our study, with respect to the prevalence of obesity. 11,14 A study done in USA during [2001][2002] showed the prevalence of overweight and obesity as 31.5 and 16.5%, respectively, for the 6 to 19…”
Section: Discussionsupporting
confidence: 88%
“…9 Another study among affluent girls in Delhi reported the prevalence of obesity and overweight to be 5.3 and 15.2%, respectively. 10 Similar studies had been conducted to assess the prevalence of overweight and obesity in India and the results are comparable to our study, with respect to the prevalence of obesity. 11,14 A study done in USA during [2001][2002] showed the prevalence of overweight and obesity as 31.5 and 16.5%, respectively, for the 6 to 19…”
Section: Discussionsupporting
confidence: 88%
“…9 A review of a few select studies during 2001 to 2012 showed a prevalence of overweight among children aged 10-19 years to be 9.9 to 19.9 per cent; high in both boys (3 to 15.1%) than in girls (5.3 to 13.3%) indicating early onset of obesity affecting more of urban school adolescents (3.4 to 6.5%) as compared to 0.6 per cent among the rural adolescents with significant gender variations. [10][11][12][13][14][15][16][17][18] Vohra R et al 19 in 2011 in Lucknow found the prevalence of overweight and obesity was 17% and 0.73% respectively among school-going children. Important correlates were children playing out-door's games for less than 30 minutes and those consuming fast food.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Moreover, it is found that adolescence is considered as one of critical time and age frames in development of obesity. [18] The adolescent period consists of growth and development physically, psychologically, and sexually, thus preparing the individual toward adulthood. Adolescents who are obese have more likelihood of becoming obese in adulthood.…”
Section: Introductionmentioning
confidence: 99%